A novel tissue inhibitor of metalloproteinases‐1/liver/cachexia score predicts prognosis of gastrointestinal cancer patients. Issue 2 (16th February 2021) - Prokopchuk, Olga; Hermann, Chris D.; Schoeps, Benjamin; Nitsche, Ulrich; Prokopchuk, Oleksii L.; Knolle, Percy; Friess, Helmut; Martignoni, Marc E.; Krüger, Achim
Abstract: Background: Cachexia, a devastating syndrome in cancer patients, critically determines survival and life quality. It is characterized by impaired homeostasis of multiple organs including the liver, involves tissue wasting, and is conventionally diagnosed and classified by weight loss (WL). However, recent studies pointed at the problem that WL is not sufficient for precise classification of cancer patients according to disease severity (i.e. prognosis). Tissue inhibitor of metalloproteinases‐1 (TIMP‐1) is an easily accessible cachexia‐associated biomarker in the blood, known to alter liver homeostasis. Here, we investigated the value of combining blood levels of TIMP‐1 with parameters of liver functionality towards establishment of a cachexia‐associated clinical score, which predicts survival of cancer patients, reflects the clinical manifestation of cachexia, and is easily accessible in the clinic. Methods: The TIMP‐1/liver cachexia (TLC) score, expressed as numerical value ranging from 0 to 1, was calculated by categorizing the blood levels of TIMP‐1 and parameters of liver functionality (C‐reactive protein, ferritin, gamma‐glutamyl transferase, albumin, and total protein) for each patient as below/above a certain risk threshold. The TLC score was tested in a cohort of colorectal cancer (CRC) patients ( n  = 82, 35.4% women, 64.6% men, median age: 70 years) and validated in a cohort of pancreatic cancer (PC) patients ( n  = 84, 54.8% women, 45.2% men, median age: 69 years). Results: In CRC patients, the TLC score positively correlated with presence of cachexia‐related symptoms (WL, impaired liver function), predicted survival [ P  < 0.001, hazard ratio (HR): 96.91 (9.85–953.90)], and allowed classification of three prognostically distinct patient subpopulations [low (LO)‐risk, intermediate (IM)‐risk, and high (HI)‐risk groups; LO vs. IM: P  = 0.003, LO vs. HI: P  < 0.001, IM vs. HI: P  = 0.029]. The prognostic power of the cachexia‐associated TLC score [ P  < 0.001, HR: 7.37 (2.80–19.49)] and its application to define risk groups (LO vs. IM: P  = 0.032, LO vs. HI: P  < 0.001, IM vs. HI: P  = 0.014) was confirmed in a cohort of PC patients. The prognostic power of the TLC score was independent of presence of liver metastases in CRC or PC patients and was superior to clinically established staging classifications. Conclusions: The TLC score, a result of straightforward determination of blood parameters, is an objective cachexia‐associated clinical tool for precise survival prediction of gastrointestinal cancer patients.